Studi Penanganan Korupsi Mengenai Pengadaan Tanah Untuk Bandara Namniwel Dalam Studi Putusan Pengadilan Negeri Ambon - Ika Puji Lestari (Sebelas Maret University, 2013)
This is a normative legal research. The approach uses qualitative approach method. Using secondary data from references including books, literature, laws and regulations, official documents, research results are intangible reports and other resources related to this research. The Data obtained analyzed with the content analysis (content analysis,) against the verdict of all the demands of the judges (Onslag Van Alle Rechts Vervolging) corruption in the procurement of land for the Airport Namniwel. Legal resources gathering techniques used in library studies and references and the internet. Research analysis used the deductive syllogism is a collection of research sources to interpret the related norms, then the research sources processed and analyzed to answer the problems examined. The last stage is to draw conclusions from the studies that were processed, so that in the end can be known why the judge threw the verdict out of all the demands of the judges (Onslag Van Alle Rechts Vervolging) corruption in the procurement of land for the Airport Namniwel. Based on the research conclusions may be drawn that in dropped verdict off against the defendant Arifin Soamole, according to judge the defendant has been proven lawfully according to law do the deed charged him as arraignment one and second of arraignment prosecutors general, but deeds the defendant was not constitute a criminal act, as in an indictment one and second and of efforts to legal be done by the prosecutors against the ruling off of them are appeal, kasasi, and review (PK) but under terms of article 244 KUHAP, accused or public prosecutor entitled to ask appeal against judgment of a court first rate against the award except free. Keywords: the argument law judge, an instrument of evidence, corruption.